INHABITING THE ROAD: PATHWAYS, AFFECTIONS, AND TEMPORARY SHELTERS - Ríos Llamas, Carlos (Benemérita Universidad Autónoma de Puebla, 2021)
The house is not a place, but a path. The objective of this article is to open the gaze to inhabit as an actthat occurs on the journey between spaces. Living, in architecture, is usually interpreted as anexperience that is determined by the analysis of a site and the subjectivity of the inhabitant. The house,in this sense, is understood as an element closely linked to its context. From an anthropologicalapproach that rescues narratives of the rarámuri house and migrant shelters, an experience of living aspart of a journey is proposed, where architecture is codified and signified from the situation of theinhabitant, changing, uprooted and constantly transit. The central argument is that life happens on theroad. Life is a constant movement that does not stop, why should the house do it? If the experience ofinhabiting imprints roots and belonging, this experience also occurs in intermediate places, inundefined spaces such as seasonal houses and temporary shelters.